2010
DOI: 10.1111/j.1472-765x.2010.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antiadhesive properties of a biosurfactant isolated fromLactobacillus paracaseissp.paracaseiA20

Abstract: Aims: The aim of this study was to determine the antimicrobial and antiadhesive properties of a biosurfactant isolated from Lactobacillus paracasei ssp. paracasei A20 against several micro-organisms, including Gram-positive and Gram-negative bacteria, yeasts and filamentous fungi. Methods and Results: Antimicrobial and antiadhesive activities were determined using the microdilution method in 96-well culture plates. The biosurfactant showed antimicrobial activity against all the micro-organisms assayed, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(203 citation statements)
references
References 20 publications
11
187
2
3
Order By: Relevance
“…A minimal reduction of 6-8 mN m 21 was observed in CFCS of CAB isolates with that of uninoculated ZMB. The small reduction observed in the surface tension implies that these strains produced low level of extracellular biosurfactants which goes well with previous report [5]. The biosurfactant producers were identified to genus and species level by 16S ribosomal RNA gene sequencing.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…A minimal reduction of 6-8 mN m 21 was observed in CFCS of CAB isolates with that of uninoculated ZMB. The small reduction observed in the surface tension implies that these strains produced low level of extracellular biosurfactants which goes well with previous report [5]. The biosurfactant producers were identified to genus and species level by 16S ribosomal RNA gene sequencing.…”
Section: Resultssupporting
confidence: 65%
“…They are also explored for their antitumor, antiviral and anti-mycoplasmic activities [3,4]. In recent years, biosurfactants are considered as potential drug candidates and looked up for their explicit biomedical applications such as antibacterial, antifungal, antiviral and antiadhesive agents against several pathogens [4][5][6][7][8]. Biosurfactants have also been proved as potential immunomodulators and enzyme inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%
“…The list includes surfactin, produced by B. subtilis, the most powerful of biosurfactant known to date. These compounds have many pharmacological activities: antibacterial, antifungal, antiviral, and antimycoplasma properties; inhibition of the fibrin clot formation and hemolysis; formation of ion channels in lipid bilayer membranes [24]; antitumour activity against Ehrlich's ascites carcinoma cells; and inhibition of the cyclic adenosine 3,5-monophosphate phosphodiesterase [25].…”
Section: Antimicrobial Activity Of Biosurfactantmentioning
confidence: 99%
“…Gudina et al [24] observed an anti-adhesive activity for the biosurfactant from Lactobacillus paracasei against several pathogenic microorganisms such as S. aureus, S. epidermidis and S. agalactiae. However, this biosurfactant showed low anti-adhesive activity against E. coli, C. albicans and P. aeruginosa, in contrast with the antimicrobial activity exhibited against these strains at the same biosurfactant concentrations.…”
Section: Anti-adhesive Activity Of Biosurfactantmentioning
confidence: 99%
“…Antibacterial activity of the crude pigment (5-0.013 mg/ml) against several microbial strains was determined by the 96-well plate microdilution method [13]. Different clinical isolates used were E. coli, Bacillus, Staphylococcus aureus, Pseudomonas aeruginosa, Shigella and Salmonella paratyphi.…”
Section: Antimicrobial Activitymentioning
confidence: 99%